The Influence of Gender on Perceptions of Culpability and Victim Status in Statutory Rape Offenses Involving Teachers. (August 2021) - Muniz, Caitlyn N.; Powers, Ráchael A.; Leili, Jennifer A.
Perceptions of child sexual abuse and statutory rape vary based on the gender of the victim, the perpetrator, and the combination of both. We extend existing research to examine attributions of responsibility and punitive preferences for student victims in student–teacher sexual relationships contingent on the gender dyad of the student and teacher and the interaction between the gender dyad and respondent gender. Participants ( N = 648) were randomly assigned to vignettes wherein the gender of the student and teacher were manipulated (female teacher/male student; female teacher/female student; male teacher/female student; male teacher/male student). Overall, respondents were "pro-victim, " though results indicate significant differences in respondent gender and how the gender dyads were perceived. Students in the male same-sex dyads were attributed less responsibility than other students. Furthermore, men were less likely to perceive the student as a victim, and women were more likely to indicate the student should be punished.